ANALISIS SUMBER DAN PENGGUNAAN KAS DAN DAMPAKNYA TERHADAP LIKUIDITAS PADA PERUSAHAAN UMUM BULOG KANTOR CABANG MAUMERE PERIODE 2017-2019 - Cicilia Ayu Wulandari Nuwa; yoseph darius purnama rangga; Imanuel Wellem; Kasilda Yuni Saputry (STEKOM PRESS, 2021)
The purposes of this research were to analyze the sources of cash, to analyze the application of cash, to analyze the liquidity level, and to analyze the effect of source and application of cash on liquidity at the National Logistical Supply Agency of Maumere Branch Office. The results of analysis showed that in the period of 2017-2018, the sources of cash weretaken from the decrease of accounts receivable, inventory of indirect material, the increase of accumulation depreciation of building and machinery, the decrease of sales revenue bank,the increased of account payable, the increase of accrued expense, the increase of regional division connection, the increase of capital, the decrease of cash. The application of cash in 2017-2018 covered the increase of down payment, merchandise inventory and tax payable. In the period of 2018-2019, the sources of cash were taken from the increase of down payment, the increase of accumulation depreciation of building and machinery, the increase of procurement payable and tax payable, the increase of accrued expense, the increaseof regional division connection. The application of cash in the period of 2018-2019 covered the increase of accounts recerivable, the increase of merchandise inventory and inventory of indirect material, the increase of prepaid expenses, the increase of sales revenue bank, the decrease of account payable, the decrease of profit or loss accumulation, and the increase of cash.Based on the results of this research, it can be conclueded that if the cash of National Logistica Supply Agency increased, the liquidity level would also increase, meanwhile if the cash of National Logistic Supply Agency descreases, the liquidity level will also decrease. Keywords: Source of Cash, Application of Cash, Liquidity